A variable cross-section test piece for evaluating the directional growth ability of TiAl-based alloys and a preparation method thereof
By designing dumbbell-shaped variable-section test pieces and using composite cold crucible directional solidification method, the problem that existing cross-section test pieces cannot evaluate the directional growth ability of TiAl-based alloys is solved, and scientific evaluation and orientation of TiAl-based alloys of different components is achieved. The solidification parameters are optimized, and the microstructure and performance of TiAl-based alloys are optimized.
Patent Information
- Application Number
- CN202311327270.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-10-13
AI Technical Summary
Existing iso-sectional test pieces cannot effectively evaluate the directional growth ability of TiAl-based alloys, and cannot reflect the impact of changes in casting cross-section on the alloy's directional solidification structure, and cannot be used for turbine blades or compressor blades with variable cross-sections in practical applications.
A dumbbell-shaped variable-section test piece was designed, prepared by the composite cold crucible directional solidification method, and different heating power and pulling rate curves were used to cause temperature field fluctuations in the test piece and form temperature field fluctuations near the paste area. The temperature gradient of the solid-liquid interface is reduced, causing interruption of columnar crystal growth and the formation of equiaxed crystal regions, thereby evaluating the directional growth ability of TiAl-based alloys of different components.
Through the design and preparation method of variable cross-sectional test pieces, the directional growth ability of TiAl base alloy can be scientifically evaluated, cost reduction, risk of engineering application, and the microstructure and comprehensive performance of the directional solidified variable cross-sectional components of TiAl base alloy can be optimized.
Smart Images

Figure CN117405484B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of directional solidification of TiAl-based alloys, and in particular relates to a variable-section test piece for evaluating the directional growth ability of TiAl-based alloys and a preparation method thereof. Background Art
[0002] The rapid development of the aerospace field in recent years has put forward new requirements for the performance of aircraft. Improving the engine thrust-to-weight ratio and operating temperature and reducing the weight of aircraft have become the inevitable development trend of aircraft and their power systems. In order to achieve weight reduction and emission reduction of aircraft engines, the use of lighter high-temperature structural materials is the most effective method. Among the existing structural materials, TiAl-based alloys have become ideal materials for aircraft engines due to their excellent properties such as high specific strength, high specific modulus, and high heat resistance. They can be used to prepare low-pressure turbine blades and compressor blades that work in the temperature range of 650-800℃.
[0003] As an intermetallic compound, TiAl-based alloy has an ordered crystal structure and a certain directionality in chemical bonds, which results in poor room temperature plasticity and processing performance, limiting its development and application in the field of aeroengines. In response to this, people have proposed directional solidification of TiAl-based alloys, taking advantage of the anisotropy of mechanical properties of TiAl-based alloy lamellar clusters, hoping to improve the room temperature plasticity and mechanical strength of TiAl-based alloys by eliminating transverse grain boundaries and controlling the lamellar orientation parallel to the loading direction.
[0004] During the directional solidification process of TiAl-based alloys, the requirements for solidification conditions are extremely high. Slight fluctuations in the temperature field may lead to interruption of directional microstructure growth, the generation of impurities, and the occurrence of problems such as banded growth, discrete growth, and island growth. In order to maintain a stable temperature field during directional solidification, the directional solidification TiAl-based alloy specimens prepared in research at home and abroad are all small-sized, simple-shaped, and uniform-section specimens. However, the turbine blades or compressor blade castings prepared from TiAl-based alloys are all variable-section, and the cross-sectional shapes and sizes at the tenons and blade bodies are different. The shape of this uniform-section specimen is far from the requirements of TiAl-based alloys in actual applications, and cannot reflect the influence of casting cross-section changes on the directional solidification microstructure of the alloy.
[0005] Moreover, TiAl-based alloys with different compositions have different directional growth abilities during the directional solidification process. When evaluating the directional growth ability of TiAl-based alloys with different alloy compositions, the temperature field of alloy specimens with equal cross-sections generally does not fluctuate, which will not have a significant impact on the directional growth process of TiAl-based alloys with different alloy compositions and cannot be used to evaluate the directional growth ability of TiAl-based alloys. Summary of the invention
[0006] In order to solve the problem that a uniform cross-section specimen cannot be used to evaluate the directional growth ability of a TiAl-based alloy, the present invention provides a variable cross-section specimen for evaluating the directional growth ability of a TiAl-based alloy and a preparation method thereof.
[0007] The technical solution of the present invention:
[0008] A variable-section test piece for evaluating the directional growth ability of a TiAl-based alloy, the variable-section test piece being a dumbbell-shaped integrated structure, and comprising, from top to bottom, a top cylinder, an intermediate cylinder, and a bottom cylinder, the top cylinder, the intermediate cylinder, and the bottom cylinder being all cylinders of equal cross-section, the cross-sectional radii of the bottom cylinder and the top cylinder being equal, the cross-sectional radius of the intermediate cylinder being smaller than the cross-sectional radii of the bottom cylinder and the top cylinder, and the variable-section test piece being made of a TiAl-based alloy.
[0009] Furthermore, the height ratio of the top cylinder, the middle cylinder and the bottom cylinder is 35:55:30.
[0010] Furthermore, the cross-sectional radius ratio of the middle cylinder to the bottom cylinder is 18:25.
[0011] Furthermore, the TiAl-based alloy is a β-solidifying TiAl alloy, a γ-TiAl alloy or a high-Nb-TiAl alloy.
[0012] Furthermore, the nominal composition of the β-solidifying TiAl alloy is Ti-42Al-6V-1Cr; the nominal composition of the conventional γ-TiAl alloy is Ti-48Al-2Cr-2Nb-0.1B, and the nominal composition of the high Nb-TiAl alloy is Ti-46Al-7Nb-0.6W-0.4Cr-0.1B.
[0013] A method for preparing a variable cross-section specimen for evaluating the directional growth ability of a TiAl-based alloy, wherein the steps of preparing the TiAl-based alloy variable cross-section specimen by a composite cold crucible directional solidification method are as follows:
[0014] Step 1: Preparation of TiAl-based alloy mother ingot:
[0015] The TiAl-based alloy is prepared by mixing the ingredients according to the nominal composition of the TiAl-based alloy and using vacuum consumable arc melting and vacuum induction melting to prepare the TiAl-based alloy mother ingot;
[0016] Step 2: Raw material preparation:
[0017] According to the shapes and sizes of the top cylinder, the middle cylinder and the bottom cylinder, TiAl-based alloy rods are cut from the TiAl-based alloy mother ingot prepared in step 1, a dovetail groove is cut at the lower end of the bottom cylinder rod, the bottom cylinder, the middle cylinder and the top cylinder rod are placed in a casting mold in sequence, and the casting mold and the TiAl-based alloy rod therein are installed in a cold crucible;
[0018] Step 3: Vacuuming:
[0019] The furnace of the composite cold crucible directional solidification system is evacuated and flushed with high-purity argon gas for gas washing;
[0020] Step 4: Directional solidification:
[0021] Start circulating water, turn on the heating power, gradually increase the heating voltage, keep warm for 5 minutes after the heating power reaches 33kW, start the automatic control system, and start pulling the specimen down. During the entire directional solidification process, the heating power and pulling rate change according to the preset curve;
[0022] After the directional solidification is completed, the specimen pulling is stopped, the power is turned off, and the specimen is taken out after cooling to room temperature to obtain a TiAl-based alloy variable cross-section specimen.
[0023] Furthermore, in step 2, when cutting the bottom column, the middle column and the top column rods from the TiAl-based alloy mother ingot, a gap of 0.5 mm in width is provided between the casting mold and the rods.
[0024] Furthermore, in step three, the furnace body of the composite cold crucible directional solidification system is evacuated until the pressure inside the furnace reaches below 5 Pa, and 300 Pa of high-purity argon gas is injected, and the gas washing is repeated three times.
[0025] Furthermore, the preset curve of the heating power during the directional solidification process in step four is that in the displacement stage of 0mm to 12mm, the heating power increases linearly from 33kW to 33.8kW; in the displacement stage of 12mm to 31mm, the heating power increases linearly from 33.8kW to 39.2kW; in the displacement stage of 31mm to 42mm, the heating power increases linearly from 39.2kW to 40kW; in the displacement stage of 42mm to 55mm, the heating power is a constant pull of 40kW; in the displacement stage of 55mm to 63mm, the heating power decreases linearly from 40kW to 39.4kW; in the displacement stage of 63mm to 90mm, the heating power decreases linearly from 39.4kW to 35kW; in the displacement stage of 90mm to 98mm, the heating power decreases linearly from 35kW to 34.6kW.
[0026] Furthermore, the preset curve of the pulling rate during the directional solidification process of step 4 is that in the displacement stage of 0mm~12mm, the pulling rate is linearly increased from 1.0mm / min to 1.05mm / min; in the displacement stage of 12mm~331mm, the pulling rate is linearly increased from 1.05mm / min to 1.59mm / min; in the displacement stage of 31mm~42mm, the pulling rate is linearly increased from 1.59mm / min to 1.66mm / min; in the displacement stage of 42mm~55mm, the pulling rate is constant at 1.66mm / min; in the displacement stage of 55mm~63mm, the pulling rate is linearly decreased from 1.66mm / min to 1.62mm / min; in the displacement stage of 63mm~90mm, the pulling rate is linearly decreased from 1.62mm / min to 1.21mm / min; in the displacement stage of 90mm~98mm, the pulling rate is linearly decreased from 1.21mm / min to 1.17mm / min.
[0027] Beneficial effects of the present invention:
[0028] During the directional solidification process, the total thermal power in the variable cross-section specimen provided by the present invention is constantly fluctuating, resulting in fluctuations in the temperature field near the mushy zone and a decrease in the temperature gradient at the solid-liquid interface, thereby causing the interruption of columnar crystal growth and the formation of equiaxed crystal zones, resulting in problems such as deflection of columnar crystal growth direction, reduced degree of organizational orientation, and increased angles and spacing of lamellae. TiAl-based alloys with weak directional growth ability are easily affected by the continuous fluctuations in the total thermal power in the variable cross-section specimen, and defects such as columnar crystal growth interruption and columnar crystal to equiaxed crystal transformation (CET transformation) are easily generated, while TiAl-based alloys with strong directional growth ability are not affected. Therefore, the directional growth ability of TiAl-based alloys with different alloy compositions and organizational structures can be scientifically predicted and evaluated, and prejudgment can be made for engineering applications in advance, reducing costs and risks.
[0029] The directional growth ability of TiAl-based alloys with different compositions is evaluated based on the continuous growth of columnar crystals, the formation of equiaxed crystal zones, the degree of deflection of columnar crystal growth direction, the degree of microstructure orientation, and the changes in the degree of orientation of lamellar microstructure of different TiAl-based alloy directional solidification variable-section specimens. This is beneficial to formulate precise directional solidification input power, pulling rate and other parameters according to the directional growth ability of different TiAl-based alloys, improve the problems of columnar crystal deflection and equiaxed crystal precipitation, and thus optimize the microstructure and comprehensive performance of TiAl-based alloy directional solidification variable-section components. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic structural diagram of a TiAl-based alloy variable cross-section test piece of the present invention;
[0031] In the figure, 1, top column; 2, middle column; 3, bottom column; 4, dovetail groove;
[0032] Figure 2 It is a schematic diagram of the installation method of the directional solidification equipment and the TiAl-based alloy variable-section test piece in the initial state of directional solidification in Example 4;
[0033] Figure 3 The comparison diagram of the magnetic induction intensity distribution on the surface of the TiAl-based alloy variable-section test piece at different pulling distances during the directional solidification process of Example 4, Figure (a) is 0 mm, Figure (b) is 28 mm, Figure (c) is 56 mm, Figure (d) is 72 mm, Figure (e) is 98 mm, and Figure (f) is 126 mm;
[0034] Figure 4 This is a simulation diagram of the heat flow direction near the variable cross-section position when the pulling distance is 28 mm in the directional solidification of Example 4;
[0035] Figure 5 The temperature gradient distribution in the TiAl-based alloy variable-section specimen at different pulling distances in directional solidification of Example 4, Figure (a) is 28 mm, Figure (b) is 56 mm, Figure (c) is an enlarged view near the variable-section position of Figure (a), and Figure (d) is an enlarged view near the variable-section position of Figure (b);
[0036] Figure 6 The microstructure photos of various positions of the conventional γ-TiAl alloy variable cross-section specimen with a pulling rate of 0.6 mm / min in Example 5;
[0037] Figure 7 The microstructure photos of various positions of the conventional γ-TiAl alloy variable cross-section specimen with a pulling rate of 1.2 mm / min in Example 5;
[0038] Figure 8 The microstructure photos of various positions of the high Nb-TiAl alloy variable cross-section test piece with a pulling rate of 0.6 mm / min in Example 5;
[0039] Fig. 9 These are microstructure photographs at various positions of the high Nb-TiAl alloy variable cross-section specimen in Example 5 with a pulling rate of 1.2 mm / min. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0041] Example 1
[0042] This embodiment provides a β-solidifying TiAl alloy variable-section specimen and a preparation method.
[0043] The variable-section test specimen of the β-solidifying TiAl alloy in this embodiment is a dumbbell-shaped integrated structure, which comprises, from top to bottom, a top cylinder 1, an intermediate cylinder 2 and a bottom cylinder 3. The top cylinder 1, the intermediate cylinder 2 and the bottom cylinder 3 are all cylinders of equal cross-section. The cross-sectional radius of the top cylinder 1 and the bottom cylinder 3 is 25 mm, the cross-sectional radius of the intermediate cylinder 2 is 18 mm, and the height ratio of the top cylinder 1, the intermediate cylinder 2 and the bottom cylinder 3 is 35 mm:55 mm:30 mm.
[0044] The nominal composition of the β-solidified TiAl alloy in this embodiment is Ti-42Al-6V-1Cr. The specific preparation method steps of the β-solidified TiAl alloy variable cross-section test piece prepared by the composite cold crucible directional solidification method are as follows:
[0045] Step 1: Preparation of β-solidified TiAl alloy mother ingot:
[0046] The ingredients are prepared according to the nominal composition of β-solidifying TiAl alloy. The raw materials used are sponge titanium (>99.95wt.%), high-purity aluminum blocks (>99.95wt.%), high-purity Cr particles (>99.95wt.%) and high-purity V particles (>99.95wt.%). Since the melting point of Al among the alloy elements is relatively low, the burnout of Al needs to be considered when preparing the ingredients. Therefore, the compensation amount of Al to offset the burnout is 5wt.%.
[0047] The conventional vacuum consumable arc melting and vacuum induction melting in the art were used to prepare the β-solidifying TiAl alloy mother ingot. After the β-solidifying TiAl alloy ingot was prepared, its alloy composition was analyzed by full spectrum direct reading plasma atomic emission spectrometer, and the actual alloy composition obtained was Ti-43.51Al-6.22V-0.95Cr.
[0048] The composite cold crucible directional solidification process used in this embodiment is developed based on the electromagnetic cold crucible directional solidification with an embedded ceramic mold. The entire directional solidification equipment consists of a heating system, a forming crystallization system, a control system, a vacuum system, a pulling system, and a cooling system. The overall equipment and the specimen installation method are as follows Figure 2 shown.
[0049] The heating system is the heat source in the directional solidification process, which is composed of a high-frequency induction power supply, a transformer, a copper crucible and an induction coil. The power supply frequency is 50kHz, and the heating power is adjustable within the range of 0 to 100kW. The forming crystallization system mainly includes a water-cooled copper crucible and a crystallizer. The water-cooled copper crucible used in this embodiment is a round crucible with a cross-sectional diameter of φ33mm and a height of 130mm. In order to allow the heating magnetic field to pass through the copper crucible wall, the side wall of the crucible is opened with 12 slits with a width of 0.5mm and filled with mica sheets. Cooling water is passed through each of the 12 petals to prevent the crucible from melting. The outer layer of the crucible is coated with epoxy resin and wrapped with insulating tape. The crystallizer contains Ga-In alloy at the bottom of the cold crucible, which is used for unilateral cooling of the directional solidification specimen to maintain the temperature gradient therein. The function of the control system is to control the directional solidification process parameters. In this embodiment, by installing an intelligent control system, the heating power and the pulling rate are automatically changed according to the preset values during the directional solidification process. Since TiAl-based alloy melts are relatively active and easily react with oxygen in the air, in order to reduce the contamination of the alloy melt, the furnace needs to be purged with a vacuum system and protected with argon before heating. The specimen pulling mechanism is composed of upper and lower pulling rods driven by an adsorption motor, which is used to accurately control the specimen pulling process for zone melting and tissue growth. During the heating process, the induction power supply, induction coil, cold crucible, furnace body and other parts will be heated by the melt or induction current, so the heat generated needs to be continuously removed through a water-cooled circulating cooling system to maintain normal working temperature.
[0050] Step 2: Raw material preparation:
[0051] According to the shape and size of the top cylinder, the middle cylinder and the bottom cylinder, the β-solidifying TiAl alloy rods are cut from the TiAl-based alloy mother ingot prepared in step 1, so that there is a 0.5 mm wide gap between the casting mold and the rods, the lower end of the bottom cylinder is cut with a dovetail groove and connected to the lower pull rod to drive the test piece to be pulled down, the β-solidifying TiAl alloy bottom cylinder, the middle cylinder and the top cylinder rods are placed in the casting mold, and the casting mold and the β-solidifying TiAl alloy rods therein are installed in a cold crucible;
[0052] Step 3: Vacuuming:
[0053] Close the furnace door and start the vacuum pump. Evacuate the furnace body of the composite cold crucible directional solidification system until the pressure inside the furnace reaches below 5Pa, and then inject 300Pa of high-purity argon gas. Repeat this three times for gas washing.
[0054] Step 4: Directional solidification:
[0055] Start circulating water, turn on the heating power, gradually increase the heating voltage, keep warm for 5 minutes after the heating power reaches 33kW, start the automatic control system, and start pulling the specimen down. During the entire directional solidification process, the heating power and pulling rate change according to the preset curve;
[0056] The preset curve of heating power during directional solidification is that in the stage of displacement 0mm~12mm, the heating power increases linearly from 33kW~33.8kW; in the stage of displacement 12mm~31mm, the heating power increases linearly from 33.8kW~39.2kW; in the stage of displacement 31mm~42mm, the heating power increases linearly from 39.2kW~40kW; in the stage of displacement 42mm~55mm, the heating power is 40kW constant pulling; in the stage of displacement 55mm~63mm, the heating power decreases linearly from 40kW~39.4kW; in the stage of displacement 63mm~90mm, the heating power decreases linearly from 39.4kW~35kW; in the stage of displacement 90mm~98mm, the heating power decreases linearly from 35kW~34.6kW. ;
[0057] The preset curve of the pulling rate during the directional solidification process is that in the displacement stage of 0mm to 12mm, the pulling rate increases linearly from 1.0mm / min to 1.05mm / min; in the displacement stage of 12mm to 331mm, the pulling rate increases linearly from 1.05mm / min to 1.59mm / min; in the displacement stage of 31mm to 42mm, the pulling rate increases linearly from 1.59mm / min to 1.66mm / min; in the displacement stage of 42mm to 55mm, the pulling rate is a constant pulling of 1.66mm / min; in the displacement stage of 55mm to 63mm, the pulling rate decreases linearly from 1.66mm / min to 1.62mm / min; in the displacement stage of 63mm to 90mm, the pulling rate decreases linearly from 1.62mm / min to 1.21mm / min; in the displacement stage of 90mm to 98mm, the pulling rate decreases linearly from 1.21mm / min to 1.17mm / min.
[0058] After the directional solidification is completed, the specimen pulling is stopped, the power is turned off, and the specimen is taken out after cooling to room temperature to obtain a β-solidified TiAl alloy variable-section specimen.
[0059] Example 2
[0060] This embodiment provides a traditional γ-TiAl alloy variable cross-section specimen and a preparation method.
[0061] The variable-section test piece of the conventional γ-TiAl alloy in this embodiment is a dumbbell-shaped integrated structure, which comprises, from top to bottom, a top cylinder 1, an intermediate cylinder 2 and a bottom cylinder 3. The top cylinder 1, the intermediate cylinder 2 and the bottom cylinder 3 are all cylinders of equal cross-section. The cross-sectional radius of the top cylinder 1 and the bottom cylinder 3 are both 25 mm, the cross-sectional radius of the intermediate cylinder 2 is 18 mm, and the height ratio of the top cylinder 1, the intermediate cylinder 2 and the bottom cylinder 3 is 35 mm:55 mm:30 mm.
[0062] The nominal composition of the conventional γ-TiAl alloy in this embodiment is Ti-48Al-2Cr-2Nb-0.1B. The specific preparation method steps of the conventional γ-TiAl alloy variable cross-section test piece prepared by the composite cold crucible directional solidification method are as follows:
[0063] Step 1: Preparation of traditional γ-TiAl alloy mother ingot:
[0064] The ingredients are prepared according to the nominal composition of traditional γ-TiAl alloy. The raw materials used are sponge titanium (>99.95wt.%), high-purity aluminum block (>99.95wt.%), high-purity Cr particles (>99.95wt.%), Al-Nb master alloy (>99.95wt.%) and Al-B master alloy (>99.95wt.%). Since the melting point of Al among the alloy elements is relatively low, the burnout of Al needs to be considered when preparing the ingredients. Therefore, the compensation amount of Al to offset the burnout is 5wt.%.
[0065] A traditional γ-TiAl alloy mother ingot was prepared by conventional vacuum consumable arc melting and vacuum induction melting in the art. After the traditional γ-TiAl alloy ingot was prepared, its alloy composition was analyzed by full spectrum direct reading plasma atomic emission spectrometer, and the actual alloy composition obtained was Ti-46.53Al-2.12Cr-2.04Nb-0.11B.
[0066] Step 2: Raw material preparation:
[0067] The shape and size of the top cylinder, the middle cylinder and the bottom cylinder are as follows: conventional γ-TiAl alloy bars are cut from the TiAl-based alloy mother ingot prepared in step 1, so that there is a 0.5 mm wide gap between the casting mold and the bar; a dovetail groove is cut at the lower end of the bottom cylinder bar and connected to a lower pull rod to drive the specimen to be pulled down; the bottom cylinder, the middle cylinder and the top cylinder bar are placed in the casting mold in sequence; the casting mold and the conventional γ-TiAl alloy bar therein are installed in a cold crucible;
[0068] Step 3: Vacuuming:
[0069] Close the furnace door and start the vacuum pump. Evacuate the furnace body of the composite cold crucible directional solidification system until the pressure inside the furnace reaches below 5Pa, and then inject 300Pa of high-purity argon gas. Repeat this three times for gas washing.
[0070] Step 4: Directional solidification:
[0071] Start circulating water, turn on the heating power, gradually increase the heating voltage, keep warm for 5 minutes after the heating power reaches 33kW, start the automatic control system, and start pulling the specimen down. During the entire directional solidification process, the heating power and pulling rate change according to the preset curve;
[0072] The preset curve of heating power during directional solidification is that in the stage of displacement 0mm~12mm, the heating power increases linearly from 33kW~33.8kW; in the stage of displacement 12mm~31mm, the heating power increases linearly from 33.8kW~39.2kW; in the stage of displacement 31mm~42mm, the heating power increases linearly from 39.2kW~40kW; in the stage of displacement 42mm~55mm, the heating power is 40kW constant pulling; in the stage of displacement 55mm~63mm, the heating power decreases linearly from 40kW~39.4kW; in the stage of displacement 63mm~90mm, the heating power decreases linearly from 39.4kW~35kW; in the stage of displacement 90mm~98mm, the heating power decreases linearly from 35kW~34.6kW. ;
[0073] The preset curve of the pulling rate during the directional solidification process is that in the displacement stage of 0mm to 12mm, the pulling rate increases linearly from 1.0mm / min to 1.05mm / min; in the displacement stage of 12mm to 331mm, the pulling rate increases linearly from 1.05mm / min to 1.59mm / min; in the displacement stage of 31mm to 42mm, the pulling rate increases linearly from 1.59mm / min to 1.66mm / min; in the displacement stage of 42mm to 55mm, the pulling rate is a constant pulling of 1.66mm / min; in the displacement stage of 55mm to 63mm, the pulling rate decreases linearly from 1.66mm / min to 1.62mm / min; in the displacement stage of 63mm to 90mm, the pulling rate decreases linearly from 1.62mm / min to 1.21mm / min; in the displacement stage of 90mm to 98mm, the pulling rate decreases linearly from 1.21mm / min to 1.17mm / min.
[0074] After the directional solidification is completed, the specimen pulling is stopped, the power is turned off, and the specimen is taken out after cooling to room temperature to obtain a traditional γ-TiAl alloy variable cross-section specimen.
[0075] Example 3
[0076] This embodiment provides a high Nb-TiAl alloy variable cross-section specimen and a preparation method.
[0077] The variable-section test piece of the high Nb-TiAl alloy in this embodiment is a dumbbell-shaped integrated structure, which includes, from top to bottom, a top cylinder 1, an intermediate cylinder 2, and a bottom cylinder 3. The top cylinder 1, the intermediate cylinder 2, and the bottom cylinder 3 are all cylinders of equal cross-section. The cross-sectional radius of the top cylinder 1 and the bottom cylinder 3 is 25 mm, the cross-sectional radius of the intermediate cylinder 2 is 18 mm, and the height ratio of the top cylinder 1, the intermediate cylinder 2, and the bottom cylinder 3 is 35 mm:55 mm:30 mm.
[0078] The nominal composition of the high Nb-TiAl alloy in this embodiment is Ti-46Al-7Nb-0.6W-0.4Cr-0.1B. The specific preparation method steps of the high Nb-TiAl alloy variable cross-section test piece prepared by the composite cold crucible directional solidification method are as follows:
[0079] Step 1: Preparation of high Nb-TiAl alloy mother ingot:
[0080] The ingredients are prepared according to the nominal composition of high Nb-TiAl alloy. The raw materials used are sponge titanium (>99.95wt.%), high-purity aluminum block (>99.95wt.%), Al-Nb master alloy (>99.95wt.%), Al-B master alloy (>99.95wt.%), high-purity Cr particles (>99.95wt.%) and high-purity W particles (>99.95wt.%). Since the melting point of Al among the alloy elements is relatively low, the burnout of Al needs to be considered when preparing the ingredients. Therefore, the compensation amount of Al to offset the burnout is 5wt.%.
[0081] The high Nb-TiAl alloy mother ingot was prepared by conventional vacuum consumable arc melting and vacuum induction melting in the art. After the high Nb-TiAl alloy ingot was prepared, its alloy composition was analyzed by full spectrum direct reading plasma atomic emission spectrometer, and the actual alloy composition obtained was Ti-46.55Al-7.5Nb-0.64W-0.38Cr-0.1B.
[0082] Step 2: Raw material preparation:
[0083] According to the shape and size of the top cylinder, the middle cylinder and the bottom cylinder, high Nb-TiAl alloy rods are cut from the TiAl-based alloy mother ingot prepared in step 1, so that there is a 0.5 mm wide gap between the casting mold and the rod, and the lower end of the bottom cylinder rod is cut with a dovetail groove and connected to the lower pull rod to drive the test piece to be pulled down, and the bottom cylinder, the middle cylinder and the top cylinder rod are placed in the casting mold in turn, and the casting mold and the high Nb-TiAl alloy rod therein are installed in a cold crucible;
[0084] Step 3: Vacuuming:
[0085] Close the furnace door and start the vacuum pump. Evacuate the furnace body of the composite cold crucible directional solidification system until the pressure inside the furnace reaches below 5Pa, and then inject 300Pa of high-purity argon gas. Repeat this three times for gas washing.
[0086] Step 4: Directional solidification:
[0087] Start circulating water, turn on the heating power, gradually increase the heating voltage, keep warm for 5 minutes after the heating power reaches 33kW, start the automatic control system, and start pulling the specimen down. During the entire directional solidification process, the heating power and pulling rate change according to the preset curve;
[0088] The preset curve of heating power during directional solidification is that in the stage of displacement 0mm~12mm, the heating power increases linearly from 33kW~33.8kW; in the stage of displacement 12mm~31mm, the heating power increases linearly from 33.8kW~39.2kW; in the stage of displacement 31mm~42mm, the heating power increases linearly from 39.2kW~40kW; in the stage of displacement 42mm~55mm, the heating power is 40kW constant pulling; in the stage of displacement 55mm~63mm, the heating power decreases linearly from 40kW~39.4kW; in the stage of displacement 63mm~90mm, the heating power decreases linearly from 39.4kW~35kW; in the stage of displacement 90mm~98mm, the heating power decreases linearly from 35kW~34.6kW. ;
[0089] The preset curve of the pulling rate during the directional solidification process is that in the displacement stage of 0mm to 12mm, the pulling rate increases linearly from 1.0mm / min to 1.05mm / min; in the displacement stage of 12mm to 331mm, the pulling rate increases linearly from 1.05mm / min to 1.59mm / min; in the displacement stage of 31mm to 42mm, the pulling rate increases linearly from 1.59mm / min to 1.66mm / min; in the displacement stage of 42mm to 55mm, the pulling rate is a constant pulling of 1.66mm / min; in the displacement stage of 55mm to 63mm, the pulling rate decreases linearly from 1.66mm / min to 1.62mm / min; in the displacement stage of 63mm to 90mm, the pulling rate decreases linearly from 1.62mm / min to 1.21mm / min; in the displacement stage of 90mm to 98mm, the pulling rate decreases linearly from 1.21mm / min to 1.17mm / min.
[0090] After the directional solidification is completed, the specimen pulling is stopped, the power is turned off, and the specimen is taken out after cooling to room temperature to obtain a high Nb-TiAl alloy variable cross-section specimen.
[0091] Example 4
[0092] This example investigates the distribution of magnetic induction intensity and temperature field on the surface of a TiAl-based variable cross-section specimen alloy during directional solidification.
[0093] The TiAl-based variable-section specimen prepared in Example 1 was Figure 2 The installation method shown is installed in the directional solidification equipment, in which H1 = 105mm, H2 = 62mm, H3 = 95mm, and H4 = 150mm. Directional solidification is carried out under the conditions of directional solidification power of 33kW and pulling speed of 1.0mm / min. When the pulling distance is 0mm, 28mm, 56mm, 72mm, 98mm and 126mm, the magnetic field distribution inside the TiAl-based alloy variable cross-section specimen and the vertical surface magnetic field induction intensity distribution curve (BZ) are monitored to obtain Figure 3 Comparison of the magnetic induction intensity distribution on the surface of TiAl-based alloy variable-section specimens at different pulling distances: (a) is 0 mm, (b) is 28 mm, (c) is 56 mm, (d) is 72 mm, (e) is 98 mm, and (f) is 126 mm.
[0094] Due to the skin effect, the magnetic field in the TiAl-based alloy variable cross-section specimen is mainly distributed within 5 mm of the surface. From the magnetic induction intensity curve on the specimen surface, it can be seen that the magnetic field will suddenly change at the variable cross-section of the specimen, such as Figure 3 The dotted line in the middle indicates the position of the curve. This is because the magnetic induction intensity is weakest at the center of the cold crucible. As the distance to the center increases, the magnetic induction intensity gradually increases. Therefore, the position with a larger diameter in the variable cross-section specimen has a greater magnetic induction intensity, which leads to a sudden change in the magnetic induction intensity at the variable cross-section. However, except for the sudden change in the magnetic induction intensity curve at the variable cross-section, the magnetic field at other positions of the specimen remains smoothly distributed, such as Figure 3 It can be seen from the BZ curve that the magnetic induction intensity on the surface of the specimen at a certain height in the cold crucible is only related to the diameter of the specimen at this point, and the magnetic induction intensity distribution on the surface of the specimen with the same diameter at the same height is also roughly the same. Therefore, in the heating area of the induction coil, the magnetic induction intensity distribution on the surface of the variable cross-section specimen can be regarded as the splicing of the magnetic field distribution curves on the surface of the rods of two diameters.
[0095] The simulation results of the temperature distribution inside the TiAl-based alloy variable-section specimen at different pulling distances during the directional solidification process of Example 4 show that as the pulling process proceeds, the high-temperature area in the specimen gradually moves upward to the top of the specimen. However, when the middle cylinder of the specimen is located in the heating area, it can be found that the high-temperature area of the specimen has shrunk significantly, and is only distributed in the range of about 20 mm above and below the center of the coil. The highest temperature in the specimen has also decreased to a certain extent, and it is not until the top cylinder above enters the heating zone that it gradually recovers. This shows that when the middle cylinder of the specimen is located in the heating area, the total thermal power of the specimen as a whole is reduced, which reduces the high-temperature area in the specimen and reduces the temperature. In this process, the fluctuation of the solid-liquid interface and the change of the temperature gradient are inevitably accompanied, which will have a certain impact on the stable growth of the organization during the directional solidification process.
[0096] When the variable cross-section of the specimen is located exactly at the center of the induction coil, the high temperature area is concentrated on the shoulder of the variable cross-section due to the skin effect. In addition, due to the shape of the specimen, the heat conduction at the shoulder of the specimen is more limited than at other locations, resulting in the formation of a heat node here. Therefore, heat is easily accumulated here. This will also have an adverse effect on the heat flow during directional solidification, such as Figure 4 The figure shows the heat flow direction near the variable cross-section position when the variable cross-section of the specimen is exactly at the center of the induction coil. As shown inside the red circle, a radial heat flow from the surface to the inside will occur here. This phenomenon does not occur at other locations of the specimen, nor is it observed in the uniform cross-section specimen prepared by cold crucible directional solidification.
[0097] In the process of heating the TiAl rod with an induction coil, due to the skin effect, the heat source in the specimen is located in the outer area of the rod. In the cold crucible directional solidification process without a mold, the material is in direct contact with the wall of the water-cooled copper crucible, resulting in strong lateral heat dissipation, so that the area with the highest temperature in the specimen is located in the center of the specimen. However, for the directional solidification process using a composite cold crucible with a mold, there is no direct contact between the material and the crucible wall, and the lateral heat dissipation is mainly achieved through convection and radiation heat transfer from the mold to the outside. In addition, the heat node on the shoulder of the specimen hinders heat transfer, so that the highest temperature point near the variable cross-section is located in the outer area of the specimen, so there is a heat flow from the outside to the inside. This may cause the directional solidification specimen to deflect at this point, thereby affecting the growth of columnar crystal structure.
[0098] Due to the appearance of steps at the variable cross-section position of the specimen, a new heat dissipation surface appears on the shoulder surface of the specimen. The heat dissipation direction of this heat dissipation surface is upward along the axial direction of the specimen, which may have a certain impact on the directional heat flow during the directional solidification process, thereby affecting the stable growth of the organization. Therefore, the heat flow of the specimen shoulder was analyzed. Figure 5The temperature gradient distribution cloud diagram is shown when the variable cross-section of the specimen is located exactly at the center of the induction coil and when the variable cross-section is located below the induction coil. Figure 5 (c) and (d) are temperature gradient distribution cloud diagrams near the variable cross-section position. It can be seen that at these two positions, the temperature gradient direction of the specimen shoulder is axially upward, that is, the heat flow direction here is upward and opposite to the axial heat flow direction required for directional solidification. The existence of this reverse heat flow may cause the growth direction of columnar crystals to deflect, and may also cause grain nucleation here, thereby causing the growth of miscellaneous crystals.
[0099] This embodiment shows that during the directional solidification process of TiAl-based alloy variable cross-section specimens, the temperature field and heat generation power will fluctuate with the increase of the pulling distance, thereby having different effects on the directional growth of TiAl-based alloy variable cross-section specimens with different compositions. Therefore, compared with traditional uniform cross-section specimens, the TiAl-based alloy variable cross-section specimens provided by the present invention can be used to evaluate the directional growth ability of TiAl-based alloys with different compositions.
[0100] Example 5
[0101] According to the alloy compositions and composite cold crucible directional solidification methods provided in Examples 1, 2 and 3, β-solidified TiAl alloy variable cross-section specimens, conventional γ-TiAl alloy variable cross-section specimens and high Nb-TiAl alloy variable cross-section specimens with the same size as in Example 4 were prepared respectively. Directional solidification was performed at a power of 33 kW, and the pulling rates were set to 0.6 mm / min and 1.2 mm / min, respectively.
[0102] The macroscopic microstructure photos of TiAl-based alloy variable-section specimens with different compositions prepared by directional solidification at different pulling rates show that the microstructure in the variable-section specimens has undergone significant changes compared with the uniform-section specimens. The length of the transition zone at the bottom of the β-solidified TiAl alloy increases. In the specimens with pulling rates of 0.6 mm / min and 1.2 mm / min, the length of the bottom transition zone is 21.3 mm and 15.7 mm, respectively, while in the uniform-section specimens under the same process parameters, the length of the transition zone is 10.5 mm and 5.1 mm, respectively. The position of the equiaxed impurity crystals in the variable-section specimens shows that the number of impurity crystals in the variable-section specimens has also increased significantly. In addition, the columnar crystals no longer maintain continuous growth. When the pulling rates are 0.6 mm / min and 1.2 mm / min, the microstructure in the β-solidified TiAl alloy enters the middle columnar area, and the columnar crystals show obvious segmentation. The precipitation of equiaxed crystals in directional solidification specimens is mainly affected by the temperature gradient and the solidification temperature range of the alloy. When the temperature gradient is low and the solidification temperature range is large, a large composition supercooling zone will appear at the front of the solid-liquid interface, causing the precipitation of free crystal nuclei in the melt and hindering the growth of columnar crystals or causing columnar crystal segmentation. In addition, the increase in the transition zone at the bottom of the specimen also shows that the directional growth of β-solidifying TiAl alloy is sensitive to slight fluctuations in heat flow. Therefore, the temperature gradient and temperature field stability must be improved to maintain the stable directional growth of β-solidifying TiAl alloy.
[0103] Columnar crystal structure can also be obtained in the variable cross-section specimen of traditional γ-TiAl alloy. The columnar crystals in the middle and lower parts of the specimen can maintain continuous and orderly growth. Due to the inevitable existence of lateral heat dissipation, it can be seen that the columnar crystals in this part are still slightly deflected inward. It is worth noting that when the columnar crystal growth reaches the variable cross-section, the continuous growth is not interrupted, but some grains are blocked by the casting mold and stop growing. However, as the columnar crystals continue to grow, equiaxed crystal zones still appear in the directional solidification variable cross-section specimen of γ-TiAl alloy, and hinder the growth of columnar crystals. In the specimens with pulling rates of 0.6mm / min and 1.2mm / min, the distance between the equiaxed crystal zone and the variable cross-section is 23.5mm and 27.5mm, respectively, and the width of the equiaxed crystal zone is 3mm and 1mm, respectively. Subsequently, under the action of unidirectional heat flow, competitive growth occurred again in the specimen, and another columnar crystal zone was formed. For the sake of convenience, C1, C2 and C3 are used to represent the area from the bottom of the specimen to the variable cross section, from the variable cross section to the equiaxed crystal region and above the equiaxed crystal region. The competitive growth process formed by C3 is called secondary competitive growth. Figure 7 (e)(f) directional solidification variable cross-section specimens of medium-high Nb-TiAl alloy. It can be seen that the growth process of its structure is roughly the same as that of traditional γ-TiAl alloy, and the phenomenon of columnar crystals first interrupting and then continuing to grow competitively occurs.
[0104] Since no continuously growing columnar crystals were formed in the variable-section specimens of β-solidifying TiAl alloy, subsequent experiments only carried out metallographic analysis of the microstructure of traditional γ-TiAl alloy variable-section specimens and high Nb-TiAl alloy variable-section specimens at different positions along the directional solidification growth direction, and investigated the growth process of columnar crystals during directional solidification of variable-section specimens of TiAl-based alloys with different alloy compositions.
[0105] Figure 6 These are microstructure photographs of various positions of a traditional γ-TiAl alloy variable-section specimen with a pulling rate of 0.6 mm / min. The enlarged image on the left is a photograph of the structure of the equiaxed crystal area and its vicinity, and the enlarged image on the right is photographs of the columnar crystal structure at different positions from top to bottom.
[0106] The E1 area in the middle of the enlarged image on the left is the equiaxed crystal zone, and the gray curve draws the boundary of the TiAl-based alloy lamellar cluster. At the bottom of the variable-section specimen, in the initial stage of directional solidification, the columnar crystals can grow normally in the bottom column after they are formed. The growth direction deflected 35 mm from the bottom of the specimen. As mentioned earlier, this was caused by the radial reverse heat flow caused by the cross-sectional change. When reaching the variable-section position, the columnar crystals at the center of the specimen can still grow normally. This is because the change in the temperature field is slowly decreasing with the overall heat generation power. When the columnar crystal grains grow to this point, the overall temperature field will not change suddenly, so it can maintain stable growth for a period of time. However, a number of irregularly shaped miscellaneous crystals appeared on the shoulder of the specimen, which is consistent with the simulation results of the temperature gradient here. There is a small axially upward temperature gradient on the shoulder of the specimen, so the nucleation and growth of the grains occurred on the casting wall, forming a number of equiaxed grains, such as Figure 6 Indicated by the arrow.
[0107] From the analysis of the temperature field below the variable cross-section position, it is known that when the grain growth reaches the variable cross-section position, the solid-liquid interface is convex and the columnar crystal deflects outward. This will also cause the growth of the columnar crystal to be blocked by the mold wall, so that it cannot continue to grow and form miscellaneous crystals. If the solid-liquid interface is concave when passing through the variable cross-section position, the grains at the edge of the specimen can grow inward under the action of lateral heat dissipation, which can alleviate the obstruction of the mold wall on the grain growth and is conducive to the continuous growth of the grains. After the columnar crystal enters the middle column 23.5mm, an equiaxed crystal zone with a width of 2.5mm appears in the directional solidification specimen, and the columnar crystal in the C2 area is completely blocked by the equiaxed crystal zone and stops growing. However, after the equiaxed crystal zone ends, competitive growth between the grains occurs immediately, and a new columnar crystal zone C3 is quickly formed. Combined with the temperature field simulation results, it can be seen that the temperature gradient reaches the lowest when the specimen is located at the top column, which causes the composition to be supercooled and the precipitation of free crystal nuclei, thereby leading to the formation of the equiaxed crystal zone. As the pulling distance continued to increase, the temperature gradient recovered after the specimen left the top column, so these equiaxed grains underwent secondary competitive growth.
[0108] Figure 7 The microstructure photos of various positions of the traditional γ-TiAl alloy variable cross-section specimen with a pulling rate of 1.2mm / min; its growth process is similar to that at a pulling rate of 0.6mm / min, but the width of the columnar crystal is significantly thinner. It is worth noting that when the pulling rate is 1.2mm / min, the number of equiaxed crystals on the shoulder of the specimen is more and the size is smaller. This is because at a larger pulling rate, the axial reverse heat flow and cooling rate of the shoulder of the specimen are greater, resulting in more grains nucleating and growing in this area. In addition, when the pulling rate is 1.2mm / min, the equiaxed crystal zone in the variable cross-section sample is significantly narrowed, and the growth of columnar crystals is not completely hindered. Multiple columnar crystals pass through the equiaxed crystal zone from the C2 region and participate in the secondary competitive growth in the C3 region.
[0109] Figure 8 and Fig. 9The microstructure photos of various positions of the high Nb-TiAl alloy variable cross-section test piece of Example 5 with pulling rates of 0.6 mm / min and 1.2 mm / min are shown; the directional solidification growth process of the high Nb-TiAl alloy in the variable cross-section casting mold is similar to that of the γ-TiAl alloy. The columnar crystals at the bottom of the test piece can maintain stable growth, and equiaxed crystal structure appears at the position where the cross section suddenly changes. After entering the middle column, the columnar crystals first stop growing, and then new columnar crystals are generated to continue to compete for growth. From the position where the columnar crystals stop growing, it can be found that at the same pulling rate, the position where the columnar crystals of the γ-TiAl alloy and the high Nb-TiAl alloy stop growing is exactly the same. At 0.6 mm / min, the position where the columnar crystals stop growing is 23.5 mm, and at 1.2 mm / min, the position where the columnar crystals stop growing is 27.5 mm / min. It can be seen that as the pulling rate increases, the distance for the columnar crystals to maintain stable growth also increases. This is because the heat generation power in the specimen begins to decrease slowly after the pulling begins. For a period of time, the overall heat dissipation of the specimen is greater than the heat generation, which causes the internal temperature gradient to decrease. When the pulling rate is high, the growth rate of the organization is also high. Therefore, when the temperature gradient is reduced to the point where it cannot maintain stable organization growth, the length of the columnar crystals that have been formed is larger. However, after the growth of the columnar crystal region in the high Nb-TiAl alloy stops, no equiaxed crystal region is formed but another columnar crystal region is formed immediately. Moreover, at pulling rates of 0.6 mm / min and 1.2 mm / min, a small amount of columnar crystals can grow continuously from the C2 region to the C3 region. This shows that under the same temperature field, the high Nb-TiAl alloy has a stronger ability of directional solidification growth.
Claims
1. A method for preparing a variable cross-section specimen for evaluating the directional growth ability of a TiAl-based alloy, characterized in that: The steps for preparing TiAl-based alloy variable cross-section specimens by composite cold crucible directional solidification method are as follows: Step 1: Preparation of TiAl-based alloy mother ingot: The ingredients are prepared according to the nominal composition of the TiAl-based alloy, wherein the TiAl-based alloy is a β-solidifying TiAl alloy, a conventional γ-TiAl alloy or a high-Nb-TiAl alloy; the nominal composition of the β-solidifying TiAl alloy is Ti-42Al-6V-1Cr; the nominal composition of the conventional γ-TiAl alloy is Ti-48Al-2Cr-2Nb-0.1B, and the nominal composition of the high-Nb-TiAl alloy is Ti-46Al-7Nb-0.6W-0.4Cr-0.1B; and the TiAl-based alloy master ingot is prepared by vacuum consumable arc melting and vacuum induction melting; Step 2: Raw material preparation: The variable cross-section test piece is a dumbbell-shaped integrated structure, which comprises, from top to bottom, a top cylinder (1), an intermediate cylinder (2) and a bottom cylinder (3), wherein the height ratio of the top cylinder (1), the intermediate cylinder (2) and the bottom cylinder (3) is 35:55:40; the top cylinder (1), the intermediate cylinder (2) and the bottom cylinder (3) are all cylinders of equal cross-section, the cross-sectional radii of the top cylinder (1) and the bottom cylinder (3) are equal, and the cross-sectional radii ratio of the intermediate cylinder (2) to the bottom cylinder (3) is 18:25; According to the shapes and sizes of the top cylinder, the middle cylinder and the bottom cylinder, TiAl-based alloy rods are cut from the TiAl-based alloy mother ingot prepared in step 1 respectively; when cutting the bottom cylinder, the middle cylinder and the top cylinder rods from the TiAl-based alloy mother ingot, a gap of 0.5 mm wide is provided between the casting mold and the rods, a dovetail groove is cut at the lower end of the bottom cylinder rod, the bottom cylinder, the middle cylinder and the top cylinder rods are placed in the casting mold in sequence, and the casting mold and the TiAl-based alloy rods therein are installed in a cold crucible; Step 3: Vacuuming: The furnace body of the composite cold crucible directional solidification system is evacuated until the pressure inside the furnace reaches below 5Pa and then 300Pa of high-purity argon gas is injected, and the gas washing is repeated three times; Step 4: Directional solidification: Start circulating water, turn on the heating power, gradually increase the heating voltage, keep warm for 5 minutes after the heating power reaches 33kW, start the automatic control system, and start pulling the specimen down. During the entire directional solidification process, the heating power and pulling rate change according to the preset curve; The preset curve of heating power is that in the displacement stage of 0mm~12mm, the heating power increases linearly from 33kW~33.8kW; in the displacement stage of 12mm~31mm, the heating power increases linearly from 33.8kW~39.2kW; in the displacement stage of 31mm~42mm, the heating power increases linearly from 39.2kW~40kW; in the displacement stage of 42mm~55mm, the heating power is 40kW constant pull; in the displacement stage of 55mm~63mm, the heating power decreases linearly from 40kW~39.4kW; in the displacement stage of 63mm~90mm, the heating power decreases linearly from 39.4kW~35kW; in the displacement stage of 90mm~98mm, the heating power decreases linearly from 35kW~34.6kW; The preset curve of the pulling rate is that in the displacement 0mm~12mm stage, the pulling rate is 1.0mm / min~1.05mm / min linearly increasing; in the displacement 12mm~331mm stage, the pulling rate is 1.05mm / min~1.59mm / min linearly increasing; in the displacement 31mm~42mm stage, the pulling rate is 1.59mm / min~1.66mm / min linearly increasing; in the displacement 42mm~55mm stage, the pulling rate is 1.66mm / min constant pulling; in the displacement 55mm~63mm stage, the pulling rate is 1.66mm / min~1.62mm / min linearly decreasing; in the displacement 63mm~90mm stage, the pulling rate is 1.62mm / min~1.21mm / min linearly decreasing; in the displacement 90mm~98mm stage, the pulling rate is 1.21mm / min~1.17mm / min linearly decreasing; After the directional solidification is completed, the specimen pulling is stopped, the power is turned off, and the specimen is taken out after cooling to room temperature to obtain a TiAl-based alloy variable cross-section specimen.
